Cost effectiveness of ixekizumab versus secukinumab in the treatment of moderate-to-severe plaque psoriasis in Spain - Johansson E; Nuñez M; Svedbom A; Dilla T; Hartz S (Dove Medical Press, 2018)
Erin Johansson,1 Mercedes Nuñez,2 Axel Svedbom,1 Tatiana Dilla,2 Susanne Hartz3 1Access, Commercialisation & Communications, ICON plc, Stockholm, Sweden; 2Health Outcomes and Real World Evidence, Eli Lilly, Madrid, Spain; 3Global Patient Outcomes and Real World Evidence International, Eli Lilly, Surrey, UK Background: Currently, several biologic agents are available for the treatment of moderate-to-severe plaque psoriasis, including newer agents with similar mechanisms of action and efficacy; therefore, there is a need to evaluate their efficiency in terms of cost effectiveness. Objective: This study evaluates the cost effectiveness of recently approved interleukin (IL)-17A antagonists, ixekizumab and secukinumab, for the treatment of moderate-to-severe plaque psoriasis from the perspective of the Spanish National Health System (NHS). Materials and methods: A Markov model with a lifetime horizon was developed to compare the cost effectiveness of ixekizumab vs. secukinumab in a hypothetical cohort of patients with moderate-to-severe plaque psoriasis. The model used monthly cycles and included four health states: a 12-week induction period, treatment maintenance, best supportive care (BSC), and death. Patients meeting response criteria at the end of the induction period transitioned to maintenance therapy, whereas non-responders transitioned to BSC. It was assumed that, each year, 20% of patients receiving maintenance therapy would discontinue treatment. The model incorporated data from various sources, including published literature, a network meta-analysis, and expert opinion for some variables. Results: Ixekizumab was dominant over secukinumab in that it gained 0.037 more quality-adjusted life years (QALYs) and saved €1951 in total costs over the lifetime horizon. Probabilistic sensitivity analysis showed a 96.6% likelihood that ixekizumab would be cost effective at a threshold of €30,000 per QALY gained. Conclusion: For the treatment of moderate-to-severe plaque psoriasis in Spain, ixekizumab provided additional QALYs and potential savings for the Spanish NHS compared with secukinumab. Since the magnitude of the differences in costs and QALYs was modest, other factors such as patient preferences (eg, for number of injections) and long-term safety (eg, related to time on the market) may also be important for guiding clinical decisions. Keywords: pharmacoeconomics, cost-utility, biologics, IL-17A antagonists